Nucleotide Sequence of Conjugative Prophage Φ1207.3 (formerly Tn1207.3) carrying the mef(A)/msr(D) genes for efflux resistance to macrolides in Streptococcus pyogenes - Iannelli, Francesco; Santagati, Maria; Santoro, Francesco; Oggioni, Marco R.; Stefani, Stefania; Pozzi, Gianni (Frontiers in Microbiology, 2014)
Genetic element Φ1207.3 (formerly Tn1207.3) is a prophage of Streptococcus pyogenes which carries the macrolide efflux resistance genes mef(A)/msr(D) and is capable of conjugal transfer among streptococci. Complete nucleotide sequence showed that Φ1207.3 is 52,491 bp in length and contained 58 ORFs. A manual homology-based annotation with functional prediction of the hypothetical gene product was possible only for 34 out of 58 ORFs. Φ1207.3 codes for two different C-methylation systems, several phage structural genes, a lysis cassette (composed by a holin and a peptidoglycan hydrolase), and three site-specific resolvases of the serine recombinase family.